Optimizing youth potential in Kwarasan Village, Magelang Regency - Luk Luk Atul Hidayati; Naufal Afiq Nur Aziz; Zulkarnain Fahmi Haris; Brenabyan Lafaredo Rakharisto; Alma Firriyal Rahman; Evi Ayu Anggraeni (Universitas Muhammadiyah Magelang, 2023)
Empowerment is an activity that is sustainable, dynamic, and synergistically encourages the involvement of all existing potentials in an evolutionary manner. The lack of knowledge and skills of young people of productive age makes them less empowered in village development. This moved the Unimma PPMT team to hold outreach and training to improve the soft skills of young people. Activities are directed at involving youth as drivers of change who have social, religious and technological abilities. The implementation method used is participatory rural appraisal (PRA) which is divided into 3 stages, namely socialization, training and mentoring as well as monitoring. The results obtained are an increase in youth productivity in; 1) social ability which is shown by the ability to adapt to the environment, attitudes in respecting others and having responsibility, 2) mental and spiritual ability which is shown in behavior in the values of worship and behaving according to norms and religion, and 3) economic ability that is demonstrated by the ability to market bamboo products using technology.